Effectivitas mass media dalam program keluarga berencana dan kependudukan di Sumatera Selatan (Lembaga Demografi, Fakultas Ekonomi, Universitas Sriwijaya, 1981)
On the effectiveness of mass media in the family planning and population programs in South Sumatra.